Exploring factors influencing number of fouls in soccer - Liu, Xuan; Zuo, Yuxin; Aslam, Hamza Saghir; Kim, Seungmo; Fu, Ming (Frontiers in Psychology, 2025)
Fouls are common events in soccer games, and their occurrence is influenced by a number of factors. Based on data from the Amisco Pro® semi-automated computer tracking system, this study explores factor influencing the numbers of fouls in soccer such as referees' running distance, foul decision distance, team strength difference, various temperature conditions, and league stages. A total of 480 soccer games from the 2018 and 2019 Chinese Super League were collected. Multiple linear regression and one-way ANOVA were employed for statistical analysis, with the significance level set at p < 0.05. The results showed that referees' running distance had a significant negative influence on the number of fouls, with R2 = 0.078. However, foul decision distance and the strength difference between teams were not significantly correlated with the number of fouls. Matches played in cool conditions (COOL, temperature < 20.0°C) had significantly more fouls than those played in hot (HOT, 25.1–30.0°C) and very hot (VHOT, >30.0°C) conditions. In contrast, no significant differences in the number of fouls were found between WARM (29.63 ± 6.72) and HOT (25.1–30.0°C) or VHOT (>30.0°C) with p > 0.05. In addition, Stage 1 had significantly fewer fouls than stage 2, with p < 0.05. On the other hand, no significant differences were found between Stage 1 and Stage 3 and between Stage 2 and Stage 3 (p > 0.05). This study highlights the impact of referees' active running on reducing the number of fouls in soccer, as well as the differences in number of fouls under various temperature conditions and stages. The findings provide insightful information for referees and the management department to anticipate the frequency of fouls and develop strategies to reduce fouls, thereby improving game quality. Future studies could explore the effects of additional environmental factors, such as stadium attendance and running track on the number of fouls.